Effectiveness of Applying Tactical Combat Casualty Care Guidelines on Paramedic's Practices. An Interventional Study - Mohammed Amen Ali, Rajaa Ibrahim Abed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: medical services provided by specialized paramedic played a key role in the military conflicts that occurred in Iraq during the last two decades after 2003 by first aid providing to the injured immediately in the battlefields to safe their life and transporting them to health care facilities for additional health care , as well as in the current study , which concerned with paramedics training on tactical combat casualty care standards that include three steps of care ( care under fire, tactical field care, and tactical evacuation care ) Objective(s): The aim of a present study is to determine the effectiveness of applying Tactical Combat Casualty Care (TCCC) guidelines on Paramedic's Practices. Methods: A pre-experimental design study was carried in Baghdad Operations Command in Iraq, at January 14th, to April 2nd, 2022. to find the effect of applying Tactical Combat Casualty Care guidelines on paramedics’ practices. Non-probability "purposive" sample of (40) paramedics are selected from all units in Baghdad Operations Commands. The questionnaire is composed of two main parts (demographic characteristics of the paramedics, and the second part involves four domains which was (71) items concerning paramedics' practices regarding the standards of Tactical Combat Casualty Care , the researcher used SPSS version 20 to analyze the data. Test-retest reliability of instrument was determined through the use of Pearson correlation coefficient and content validity of the instrument was determined through a panel of (fourteen) experts. Data was analyzed through the use of descriptive and inferential statistical analysis. Results: The results of paramedic's practices in overall main domains related to applying TCCC standards was inadequate in pretest , while in posttest I results showed that the paramedics' practices was improved to adequate level after application of the intervention program . Then the posttest II was done, and the results was similar to posttest I. the data show that there were highly significant differences between pre and post test , which emphasis the positive effect of program. Conclusion: The study concluded that there was improvement in paramedics' practices toward the TCCC intervention program. Recommendation: The study recommended to Continuous training for paramedics and engages them in courses, seminars, and conferences to improve their skills and information.